Community activities and the impacts on the environment at Krau Wildlife Reserve, Malaysia / Che Bon Ahmad, Jamalunlaili Abdullah and Jasmee Jaafar - Ahmad, Che Bon; Abdullah, Jamalunlaili; Jaafar, Jasmee (Universiti Teknologi MARA Cawangan Selangor, 2018)
Protected Areas (PAs) are signißcantfor ecosystem and communities. Studies suggested that land use activities carried out by the community surrounding the PAs could increase the pressure to the latter. Thus, this study is to identify the land use activities carried out by them, and to ascertain its spatial impact towards KWR. This study chooses a RS techniques and ground verißcation using GPS. 7he ßndings conßrm that there are land use activities performed by the communities, mostly on flat and less at hilly and undulating areas. Large scale plantations and encroachment are the major impact on the KWR.